CD138 and CD31 Double-Positive Cells Comprise the Functional Antibody-Secreting Plasma Cell Compartment in Primate Bone Marrow - Martinez-Murillo, Paola; Pramanik, Lotta; Sundling, Christopher; Hultenby, Kjell; Wretenberg, Per; Spångberg, Mats; Karlsson Hedestam, Gunilla B. (Frontiers in Immunology, 2016)
Abstract Plasma cells (PCs) are defined as terminally differentiated B cells that secrete large amounts of immunoglobulin (Ig). Plasma cells that reside in the bone marrow (BM) are responsible for maintaining long-term antibody responses after infection and vaccination, while plasma cells present in the blood are generally short-lived. In rhesus macaques, a species frequently used for the evaluation of human vaccines, B cells resemble those found in humans. However, a detailed characterization of BM-resident rhesus plasma cell phenotype and function is lacking. Here, we examined Ig secretion of distinct rhesus CD138+ populations by B cell ELISpot analysis to couple phenotype with function. We demonstrate that the CD20low/-CD138+CD31+ BM population was highly enriched for antibody-secreting cells with IgG being the predominant isotype (60%), followed by IgA (33%) and IgM (7%). Transmission electron microscopy (TEM) analysis confirmed plasma cell enrichment in the CD20low/-CD138+CD31+ population with cells containing nuclei with “spokes of a wheel” chromatin structure and prominent rough endoplasmic reticulum. This panel also stained human BM PCs and allowed a clear distinction between BM PCs and short-lived peripheral plasma cells, providing an improved strategy to isolate PCs from rhesus bone marrow for further analysis.